Seismic Expression of Geological Features in Seram Sea: Seram Trough, Misool-Onin Ridge and Sedimentary Basin - Darman, Herman; Reemst, Paul (Berita Sedimentologi, 2012)
The Seram Sea is located between Seram Island and the Bird’s Head of Papua, Eastern Indonesia. This sea extends to the east towards Bintuni Bay. Some part of the sea, between Seram and Misool are deeper than 2000 m. The Seram Island is mountainous with altitudes reaching 3000 m above sea level at the center of the island.Several seismic surveys have been conducted to understand the geology of this region. The first seismic sections were published by Hamilton in 1979. These seismic sections were acquired by Western Geophysical for Phillips Petroleum. In 2000, Schlumberger published some seismic lines acquired in 1997 with an improved resolution improvement. More higher quality seismic lines were acquired as part of non exclusive and multi-client projects in the late 1990’s which provide a better geological understanding of the region and lead to several petroleum exploration opportunities.This article discusses the seismic expression of several geological features in the Seram Sea vicinity based on published seismic sections. The offshore seismic sections cover part of the imbricated complex in the north of Seram Island, the Seram Trough, the Misool-Onin High and the sedimentary basins the east of the Misool-Onin Ridge, such as the Tamaloi-Malagot Basin, the Semai-Berau Basin and the Bintuni Basin.